Pengaruh Latihan Passing Bawah Berpasangan Terhadap Kemampuan Passing Bawah Pemain Bola Voli Bintang Siantar Klub - Nasution, Taufiq Hidayat; Nusri, Ardi; Novita, Novita (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the effect of paired lower passing training on the lower passing ability of Volleyball players Bintang Siantar Klub. The research problem is the low lower passing ability of Bintang Siantar Klub volleyball players. From the data analysis conducted, it is known that the paired lower passing training model has a significant effect on the lower passing ability of volleyball. Where the obtained mean difference test (t test) is 14.409 while the t table is 2.201 with a significant level of α = 0.05 and n = 12, then tcount> t table (14.409> 2.201), so it can be concluded that there is a significant effect of the paired lower passing training model on the lower passing ability of volleyball players Bintang Siantar Klub. Keywords : Lower Passing and Volleyball